THE INFLUENCE OF PERCEPTION OF ORGANIZATIONAL JUSTICE , QUALITY OF WORK LIFE AND ORGANIZATIONAL COMMITMENT ON PERFORMANCE : (Study on Kayen and Jaken Public Health Center Employees) - Rahmawati, Salis Diah; Priyono, Bambang Suko (IJOSMAS, 2022)
The purpose of this study was to analyze the effect of perceived organizational justice and quality of work life on performance by mediating organizational commitment. This research is a quantitative research. Primary data was obtained from questionnaire answers from each respondent using google form with data processing tools using SPSS software. The results of the questionnaire recapitulation obtained 115 respondents' answers which were then analyzed for data. There were 115 employees at the Kayen and Jaken Public Health Center as the population in this study. Based on the results of data analysis, it was concluded that the perception of organizational justice has a significant influence on organizational commitment of employees at the Puskesmas, the quality of work life has a significant influence on organizational commitment of employees at the Public Health Center, the perception of organizational justice has a significant influence on the performance of employees at the Public Health Center, Quality of work life has a significant effect on performance, organizational commitment has a significant effect on performance, organizational commitment mediates the effect of perceived organizational justice and quality of work life on performance.